Genetic insights into the evolution of genera with the eastern Asia–eastern North America floristic disjunction: a transcriptomics analysis. Issue 12 (6th December 2020) - Melton, Anthony E.; Chen, Shichao; Zhao, Yunpeng; Fu, Chengxin; Xiang, Qiu‐Yun (Jenny); Cheng, Shifeng; Wong, Gane K.‐S.; Soltis, Pamela S.; Soltis, Douglas E.; Gitzendanner, Matthew A.
Abstract : Premise: Large disjunctions in species distributions provide excellent opportunities to study processes that shape biogeographic patterns. One such disjunction is the eastern Asia–eastern North America (EA‐ENA) floristic disjunction. For many genera with this disjunction, species richness is greater in EA than in ENA; this pattern has been attributed, in part, to higher rates of molecular evolution and speciation in EA. Longer branch lengths have been found in some EA clades, relative to their ENA sister clades, suggesting that the EA lineages have evolved at a higher rate, possibly due to environmental heterogeneity, potentially contributing to the species richness anomaly. Methods: To evaluate whether rates of molecular evolution are elevated in EA relative to ENA, we used transcriptomes from species in 11 genera displaying this disjunction. Rates of molecular evolution were estimated for up to 385 orthologous nuclear loci per genus. Results: No statistically significant differences were identified in pairwise comparisons between EA and ENA sister species, suggesting equal rates of molecular evolution for both species; the data also suggest similar selection pressures in both regions. For larger genera, evidence likewise argues against more species‐rich clades having higher molecular evolutionary rates, regardless of region. Our results suggest that genes across multiple gene ontology categories are evolving at similar rates under purifying selection in species in both regions. Conclusions: Our data support the hypothesis that greater species richness in EA than ENA is due to factors other than an overall increase in rates of molecular evolution in EA.